Fatores prognósticos para a metástase no melanoma cutâneo - Ana Carolina Figueiredo Pereira (2013)
BACKGROUND: Malignant melanoma is a neoplasm that shows high mortality when diagnosed in advanced stages. Its incidence has increased worldwide and, although solid progress has been noted in the therapy of metastatic tumors in recent years, disseminated cases still carry guarded prognostic. Therefore, the premature identification of high-risk patients to develop melanoma metastasis is the main strategy to reduce mortality. OBJECTIVE: To assess the influence of eight clinical, epidemiological and histopathologic features on the development of metastasis in patients diagnosed with invasive primary cutaneous melanoma. METHODS: Our historical cohort comprised patients with invasive primary cutaneous melanoma seen between January 1995 and January 2012 at a public university hospital (Hospital das Clínicas, Federal University of Minas Gerais, Belo Horizonte, Brazil) and a private institution (Oncologia Cirúrgica do Aparelho Digestivo, Belo Horizonte, Brazil), and followed up for at least one month. The following variables were analyzed: gender, age at diagnosis, family history of melanoma, anatomic site of the tumor, histologic subtype, Breslow thickness, histologic ulceration and the presence of mitosis. Kaplan-Meier univariate test and multivariate Cox proportional hazard analysis [Hazard Ratio (HR)] were used to assess factors associated with disease-free survival. RESULTS: Five hundred and fourteen patients were enrolled. Of all, 135 (26.3%) developed metastasis. The univariate analysis included all individuals, and the following significant risk factors were identified: gender (p = 0.0007), age at diagnosis (p = 0.0566), anatomic site of the tumor (p = 0.0054), histologic subtype (p < 0.0001), Breslow thickness (p < 0.0001), histologic ulceration (p < 0.0001) and presence of mitosis (p < 0.0001). The variable family history of melanoma did not reach statistical significance. Multivariate analysis detected four significant prognostic factors (p < 0.05): male gender (HR = 2.15; female gender: HR = 0.46, IC 95% 0.24-0.90, p = 0.0222), nodular histologic subtype (HR = 2.89, IC 95% 1.19-7.03, p = 0.0196), Breslow thickness > 4 mm (HR = 7.85, IC 95% 2.27-27.16, p = 0.0011) and presence of ulceration (HR = 2.14, IC 95% 1.04-4.40, p = 0.0391). Presence of mitosis was not included at this analysis, explained by the lack of metastases in those tumors without mitoses in the histologic exam. The risk of metastasis for the 215 patients with complete data on the seven variables statistically significant at the univariate analysis, including the presence of mitosis, was also calculated. The results were similar, except for Breslow thickness between 1 and 4 mm, which was also considered statistically significant (p = 0.0113). CONCLUSIONS: The following prognostic factors to the development of melanoma metastasis were identified in the study: male gender, nodular histologic subtype, Breslow thickness > 4 mm and ulceration. These results are similar to other reports in the literature. Presence of mitosis was statistically significant at the univariate analysis. Age, family history of melanoma and anatomic site of the tumor were not considered risk factors in our data.